2018
DOI: 10.1021/acs.analchem.8b03557
|View full text |Cite
|
Sign up to set email alerts
|

Next Generation Sequencing Analysis of Total Small Noncoding RNAs from Low Input RNA from Dried Blood Sampling

Abstract: Circulating miRNAs are favored for biomarker candidates as they can reflect tissue specific miRNA dysregulation in disease contexts. Moreover, they have the additional advantage that they can be monitored in a minimally invasive manner. Blood-borne miRNAs are therefore currently characterized to identify, describe, and validate their potential suitability as biomarkers; however, sampling and as well miRNA detection methods limit these studies in terms of sensitivity but also practicability in clinical, at-home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
0
10
0
1
Order By: Relevance
“…Second, there have long existed protocols to separate the total pool of miRNAs from other transcripts [ 31 33 ], without the need for specific primers or probes. Third, miRNAs are very stable transcripts [ 34 ], detectable even in minute dried blood samples [ 35 ] or from samples several thousands of years old [ 36 ]. All these features combined make miRNAs very promising markers at the RNA level.…”
Section: Discussionmentioning
confidence: 99%
“…Second, there have long existed protocols to separate the total pool of miRNAs from other transcripts [ 31 33 ], without the need for specific primers or probes. Third, miRNAs are very stable transcripts [ 34 ], detectable even in minute dried blood samples [ 35 ] or from samples several thousands of years old [ 36 ]. All these features combined make miRNAs very promising markers at the RNA level.…”
Section: Discussionmentioning
confidence: 99%
“…Deeper coverage will assist the analysis of rare sequences and give more confidence in the number of reads per transcript. Recently, it was reported that the classic ligation dependent library preparation method was biased to miRNAs [44], which calls for consideration of more recently developed methods such as capture and amplification by tailing and switching (CATS) [45,46]. During the data analysis phase, different algorithms/ calibration methods should be applied to characterize overlapping targets in order to improve the result confidence.…”
Section: Ev Omics Analysis and Biomarker Discoverymentioning
confidence: 99%
“…Eine Herausforderung für Hochdurchsatzsequenzierungen von miRNAs auf Basis von DBS war in der Vergangenheit sicherlich die sehr geringe Menge an kapillarem Blut und damit die geringe Menge an enthaltener RNA. Im Zuge der Entwicklung neuerer Protokolle gibt es jedoch erste Ansatzpunkte, die zukünftig die Hochdurchsatzsequenzierung von miRNAs auf Basis von DBS ermöglichen könnten [15].…”
Section: Biomarkerunclassified